2021
DOI: 10.1016/j.clinbiomech.2020.105204
|View full text |Cite
|
Sign up to set email alerts
|

A uniaxial force and stiffness model of the vagina during laparoscopic sacrocolpopexy

Abstract: Background: Laparoscopic sacrocolpopexy is the preferred procedure for restoring vaginal vault prolapse. An assistant uses a vaginal manipulator to position and tension the vault such that the surgeon can dissect the bladder, rectum and vault to eventually suture a synthetic mesh used to suspend the vagina to the longitudinal anterior vertebral ligament. Vaginal vault manipulation requires application of high forces for long periods of time.Methods: This work quantifies the task by measuring and analyzing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Although the human assistant is able to feel the forces applied to the vault, this information is rarely fed back to the main surgeon. During a previous study [12] it was observed that the main surgeon is most often concerned with having proper vault exposure rather than possible overtensioning. Therefore, communication between main surgeon and vaginal manipulator assistant is mostly unidirectional and consists of giving positioning instructions to the assistant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the human assistant is able to feel the forces applied to the vault, this information is rarely fed back to the main surgeon. During a previous study [12] it was observed that the main surgeon is most often concerned with having proper vault exposure rather than possible overtensioning. Therefore, communication between main surgeon and vaginal manipulator assistant is mostly unidirectional and consists of giving positioning instructions to the assistant.…”
Section: Discussionmentioning
confidence: 99%
“…According to Akrivos and Barton-Smith, the ViKY UP provides a reduced range of motion when manipulating loads greater than 350 g [8]. This is insufficient for LSC as vaginal vault tensioning forces higher than 20 N have been measured [12].…”
Section: B Robot-assisted Surgerymentioning
confidence: 99%
See 1 more Smart Citation